Ethical Leadership in the Military Profession and the “Dirty Hands” Problem in Contemporary Armed Conflicts - Stanar, Dragan (The Policy of National Security, 2024)
In this paper author explores the possibility and implications of the emergence of the ethical problem of “dirty hands” outside of the context of political decision-making in the narrower sense, more precisely in the context of decisions made by members of the military profession in war. By shortly analysing the nature of decision-making in war, the author determines an undisputable political character of war and, thus, the political implication of the decisions of military leaders. By notion-analysis of the phenomenon of “dirty hands”, the author defines its explicit attributes and then applies them to the decision-making process of military leaders in war. By pointing out the characteristic circumstances under which the problem is generated in war and by creating an analogy with the sphere of political decision-making, the author defines two specific situations in which this problem can only occur – supreme emergency and collateral damage. The author proves that in situations of supreme emergency and collateral damage, all necessary conditions for the constitution of this ethics problem for military leaders who make political decisions in war are met and, in conclusion, offers an explanation of the importance and relevance of precise definition of the place and nature of the problem of “dirty hands” in the process of ethical leadership for proper perception of the moral nature of military profession in the contemporary era.